7.4k views
0 votes
If f(x)=x^2+2x−5 and g(x)=2x+4, what is (f⋅g)(x)

User JP Foster
by
7.1k points

2 Answers

4 votes

Answer:

Explanation:

f(x)=x²+2x−5 and g(x)=2x+4

(f⋅g)(x) = (x²+2x−5)(2x+4) = 2x^3 +4x² -10x +4x²+8x-20

(f⋅g)(x) = 2x^3+8x² -2x -20

User Kalan Nawarathne
by
7.0k points
5 votes

For this case we have the following functions:


f (x) = x ^ 2 + 2x-5\\g (x) = 2x + 4

We must find
(f * g) (x). By definition we have to:


(f * g) (x) = f (x) * g (x)

So:


(f * g) (x) = (x ^ 2 + 2x-5) (2x + 4)

Applying distributive property we have:


(f * g) (x) = 2x ^ 3 + 4x ^ 2 + 4x ^ 2 + 8x-10x-20

We add similar terms:


(f * g) (x) = 2x ^ 3 + 8x ^ 2-2x-20

Answer:


(f * g) (x) = 2x ^ 3 + 8x ^ 2-2x-20

User Inigo EC
by
7.3k points